Integration of algae‐based biofuel production with an oil refinery: Energy and carbon footprint assessment. (22nd July 2020) - Andersson, Viktor; Heyne, Stefan; Harvey, Simon; Berntsson, Thore
Summary: Biofuel production from algae feedstock has become a topic of interest in the recent decades since algae biomass cultivation is feasible in aquaculture and does therefore not compete with use of arable land. In the present work, hydrothermal liquefaction of both microalgae and macroalgae is evaluated for biofuel production and compared with transesterifying lipids extracted from microalgae as a benchmark process. The focus of the evaluation is on both the energy and carbon footprint performance of the processes. In addition, integration of the processes with an oil refinery has been assessed with regard to heat and material integration. It is shown that there are several potential benefits of co‐locating an algae‐based biorefinery at an oil refinery site and that the use of macroalgae as feedstock is more beneficial than the use of microalgae from a system energy performance perspective. Macroalgae‐based hydrothermal liquefaction achieves the highest system energy efficiency of 38.6%, but has the lowest yield of liquid fuel (22.5 MJ per 100 MJalgae ) with a substantial amount of solid biochar produced (28.0 MJ per 100 MJalgae ). Microalgae‐based hydrothermal liquefaction achieves the highest liquid biofuel yield (54.1 MJ per 100 MJalgae ), achieving a system efficiency of 30.6%. Macro‐algae‐based hydrothermal liquefaction achieves the highest CO2 reduction potential, leading to savings of 24.5 resp 92 kt CO2eq /year for the two future energy market scenarios considered, assuming a constant feedstock supply rate of 100 MW algae, generating 184.5, 177.1 and 229.6 GWhbiochar /year, respectively. Heat integration with the oil refinery is only possible to a limited extent for the hydrothermal liquefaction process routes, whereas the lipid extraction process can benefit to a larger extent from heat integration due to the lower temperature level of the process heat demand. Abstract :